1998
DOI: 10.1172/jci4174
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional consequences of alveolar cell recognition by CD8(+) T lymphocytes in experimental lung disease.

Abstract: CD8ϩ T cells infiltrate the lung in many clinical conditions, particularly in interstitial lung disease. The role(s) that CD8 ϩ T cells might be playing in the pathogenesis of inflammatory lung disease is unclear at present, as is the direct contribution of CD8 ϩ T cell effector activities to lung injury. This report describes a transgenic model used to evaluate the impact, on respiratory structure and function, of CD8 ϩ T lymphocyte recognition of a target antigen expressed endogenously in alveolar epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
84
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 36 publications
6
84
0
1
Order By: Relevance
“…Moreover, an effector cytokine profile has been detected in CD8 + T cells isolated from patients with pulmonary disorders; the presence of these cytokines suggests that T cytotoxic type 1 (Tc1) cells make an important contribution to the pathologic findings associated with lung diseases (5,6). This finding was further supported by experimental data obtained from the adoptive transfer of Tc1 cells specific for a neo self-antigen expressed in the lungs of recipient mice; the transfer led to severe pulmonary inflammation and lethality within a few days (7).…”
supporting
confidence: 53%
“…Moreover, an effector cytokine profile has been detected in CD8 + T cells isolated from patients with pulmonary disorders; the presence of these cytokines suggests that T cytotoxic type 1 (Tc1) cells make an important contribution to the pathologic findings associated with lung diseases (5,6). This finding was further supported by experimental data obtained from the adoptive transfer of Tc1 cells specific for a neo self-antigen expressed in the lungs of recipient mice; the transfer led to severe pulmonary inflammation and lethality within a few days (7).…”
supporting
confidence: 53%
“…The potential for activated T-cells to cause lung injury in mice was evidenced after adoptive transfer of CD8 + T-cells with specifi cities for neoantigens that were expressed on alveolar epithelial cells (Enelow et al 1998). CD8 + T-lymphocytes were also recently shown to be critical for the induction of infl ammation and tissue destruction in a murine model of smoke-induced emphysema (Maeno et al 2007).…”
Section: Associations Of T-lymphocytes With Copdmentioning
confidence: 99%
“…However, it is difficult to separate the direct effects of the viral infection on lung pathology from the effects of the CD8 ϩ T cell effector functions, such as cytotoxicity and production of the proinflammatory cytokines IFN-␥ and TNF-␣. Using a transgenic mouse model of influenza infection in which influenza hemagglutinin (HA) is expressed by lung epithelial cells (6), we have identified critical mechanisms by which CD8 ϩ T cells mediate influenza immunopathology in the absence of replicating virus. We previously demonstrated that, following alveolar antigen recognition, TNF-␣ production by HA-specific CD8 ϩ T cells induced lung epithelial cell chemokine expression, which resulted in extensive airway inflammation and lethal lung injury (4,32).…”
mentioning
confidence: 99%